PENGUATAN LITERASI KEBENCANAAN MELALUI PROGRAM SIPANDAI PADA SISWA SEKOLAH DASAR - Yuliani, Rostika; Rizki, Diyah Pitaloka (Unpad Press, 2026)
Disaster literacy among elementary school students is a crucial component of disaster risk reduction efforts, particularly in Indonesia, which is highly vulnerable to earthquakes. However, students’ understanding of disaster risks, mitigation measures, and self-protection procedures remains limited and requires systematic and sustainable educational interventions. This community service program aimed to enhance disaster literacy and preparedness among students through the Students for Disaster Awareness and Response in Indonesia (SIPANDAI) Program. The program was implemented at Rancakasumba Private Elementary School in Bandung, involving 28 fourth-grade students. A combination of community education and training methods was employed using a participatory approach. Activities included needs assessment, development of educational materials, interactive awareness sessions, introduction to emergency preparedness kits, earthquake response simulations, and evaluation through observation and activity documentation. The results indicated that students gained a better understanding of the causes and impacts of earthquakes, recognized appropriate mitigation measures, and demonstrated proper self-protection actions during simulation exercises. Active participation in discussions, quizzes, and simulations also reflected increased awareness of the importance of disaster preparedness from an early age. In addition to benefiting students, the program strengthened the role of higher education institutions in promoting community-based disaster education. Therefore, the SIPANDAI Program proved to be an effective educational medium for improving disaster literacy and preparedness among elementary school students as part of broader disaster risk reduction efforts.